2020
DOI: 10.1037/neu0000682
|View full text |Cite
|
Sign up to set email alerts
|

Differential impairments in irony comprehension in brain-damaged individuals: Insight from contextual processing, theory of mind, and executive functions.

Abstract: Objective: The comprehension of irony can be affected after brain injuries. The cognitive mechanisms accounting for such disorders remain yet unclear. The heterogeneity of cognitive profiles of brain-damaged individuals and the use of independent tests to measure the links between these mechanisms and the comprehension of irony might contribute to this lack of clarity. The present study aimed to further explore the underlying mechanisms of irony understanding disorders (i.e., context processing, executive func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 72 publications
(142 reference statements)
2
15
2
Order By: Relevance
“…One of the goals of the IRRI test is to help clinicians identify the cognitive impairment underlying poor comprehension of non-literal language (i.e., the context processing, EF, and ToM), responsible for the heterogeneity of performances amongst ABI participants (Blake, 2017;Champagne-Lavau et al, 2018;Champagne-Lavau & Joanette, 2009;Cordonier et al, 2020). To this end, each scenario was divided into six conditions by manipulating three factors.…”
Section: Study 1 Development Of the Irri Testmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the goals of the IRRI test is to help clinicians identify the cognitive impairment underlying poor comprehension of non-literal language (i.e., the context processing, EF, and ToM), responsible for the heterogeneity of performances amongst ABI participants (Blake, 2017;Champagne-Lavau et al, 2018;Champagne-Lavau & Joanette, 2009;Cordonier et al, 2020). To this end, each scenario was divided into six conditions by manipulating three factors.…”
Section: Study 1 Development Of the Irri Testmentioning
confidence: 99%
“…Two pilot studies were conducted to identify the occupation stereotypes added in the ironic conditions with cues and to select the scenarios for the final version. These pilot studies were reported in Cordonier et al (2020). At the end of these pilot studies, 18 scenarios with a high success rate were selected for the final version of the task.…”
Section: Construction Of the Irony Taskmentioning
confidence: 99%
See 3 more Smart Citations